Reflexos da terceirização na ordem jurídica e suas repercussões nas instituições bancárias públicas do Brasil - Farias, Raquel Maria Azevedo Pereira (2017)
Outsourcing represents a phenomenon resulting from the dynamics of the business relations, which change throughout time, whether are they in virtue of social conquests, as the end of slavery, or due to the surging of new economical processes and systems such as globalization and neoliberalism. These are some amongst so many factors that contribute to the search for new production techniques aiming to provide business competitiveness and reach the biggest possible profitability. It happens that such phenomenon was inserted in our country by means of multinationals without any national regulation, being, therefore, used solely in benefit of companies, under a fragile speech of generation of employments. In this scenario, outsourcing in public banking institutions in Brazil increases every year, mitigating the banking class and demeaning the workers’ rights, who accomplish banking activities, however not inserted in the trilateral relation of outsourcing, and do not do justice to any protection of the said class. For these reasons, it is imperative a theoretical construction to analyze whether the use of outsourcing in public banking institutions in Brazil co-ordinates with the constitutional text and international standards that concern work, from the Law Project 30/2015, which intends to regularize all types of outsourcing without violating the social value of work and preventing the sustainable development. By mean of a deductive approach and historical process it is possible to understand the phenomenon of outsourcing, its origin and development, as well as construct historical reflection of work in Brazil until the contemporary scenario and, at last, by accomplishing an exploratory research, analyzing rules, principles, jurisprudences and judicial decisions, it has been found that outsourcing in public banking institutions do not promote sustainable development, and if the said Law Project is approved as proposed, it will reveal a patent social kickback.